Розроблення приводу установки катафорезу підігрівачів - Павлюк, Андрій Михайлович; Pavliuk, Andrii Mykhailovych (Національний університет "Львівська політехніка", 2024)
Робота містить пояснювальну записку та графічну частину. Поясню-вальна записка складається зі вступу, технологічної, конструкторської час-тин, додатків з: економічною частиною, охороною праці та специфікаціями до графічної частини. У технологічній частині проведений аналіз видів покрить, що засто-совуються в електронному приладобудуванні. Оксидний катод є однією з частин електровакуумного приладу, на які наноситься емісійні та ізоляційні покриття. В катодів непрямого розжа-рення у нагрівання здійснюється спеціальним підігрівачем, що розташова-ний в порожнині катода та ізольований від його металевої частини. Емісій-ні покриття наносять зовнішню бокову або торцеву поверхню керна. Піді-грівач покривається ізоляційним покриттям (алундом) [3]. Розглянуті методи нанесення покрить на деталі електронних прила-дів. Нанесення покрить методом пульверизації полягає в розпиленні су-спензій або рідких складів з допомогою стисненого повітря спеціальними пульверизаторами. Другий метод нанесення покрить – катафорез. У виро-бництві електровакуумних приладів метод катафорезу застосовується для нанесення алундових покрить на підігрівачі катодів, карбонатних покрить на оксидні катоди та газопоглинаючих цирконієвих і торієвих покрить на відповідні деталі приладів. Третій метод нанесення покрить -плазмовий метод, що полягає в розплавленні та переносі карбонатів на керни катодів, що охолоджуються. У конструкторській частині приведено опис конструкції та принципу дії напівавтомата катафорезу підігрівачів. Напівавтомат катафорезного покриття підігрівачів призначений для покриття складних підігрівачів алундом методом катафорезу. Це багатопозиційна машина з періодичної дій. Касета з підігрівачами періодично переміщається між позиціями ма-шини, на яких здійснюються операції. На даному напівавтоматі здійснюються наступні операції: катафорез-не покриття підігрівачів; промивання підігрівачів в ацетоні для видалення капель алундової пасти та затікань, що утворюються в петлях підігрівача; сушка покриття в струмені гарячого повітря; закріплення покриття для підвищення його механічної міцності; кінцева остаточна сушка. Проведений розрахунок кінематичної та пневматичної схем машини, розрахунок потужності приводу каруселі та автомата, розраховані маль-тійський механізм приводу каруселі, пасова та черв’ячна передачі [1,2]. В графічній частині проекту приведені кінематична схема машини, загальний вид машини з приводом, механізм приводу, робочі креслення двох деталей, специфікації до складального креслення. В економічній частині визначена економічність машини для у виго-товленні та експлуатації, визначена доцільність його розробки. В розділі «Охорона праці» розроблені заходи по покращенню робо-ти напівавтомата катафорезу підігрівачів з точки зору техніки безпеки.розрахунок, економіка, безпека.

The work contains an explanatory note and a graphic part. The explana-tory note consists of an introduction, technological, design parts, appendices with: economic part, labor protection and specifications for the graphic part. In the technological part, an analysis of the types of coatings used in elec-tronic instrument making is carried out. The oxide cathode is one of the parts of an electrovacuum device on which emission and insulating coatings are applied. In indirect heating cathodes, heat-ing is carried out by a special heater located in the cavity of the cathode and isolated from its metal part. Emissive coatings are applied to the outer side or end surface of the core. The heater is covered with an insulating coating (alun-dum) [3]. The methods of applying coatings to parts of electronic devices are con-sidered. Applying coatings by the spray method consists in spraying suspen-sions or liquid compositions using compressed air with special spray guns. The second method of applying coatings is cataphoresis. In the production of electrovacuum devices, the cataphoresis method is used to apply alundum coatings to cathode heaters, carbonate coatings to oxide cathodes, and gas-absorbing zirconium and thorium coatings to the corresponding parts of the devices. The third method of applying coatings is the plasma method, which consists in melting and transferring carbonates to the cooled cathode cores. The design part describes the design and principle of operation of a semi-automatic cataphoresis heater. The semi-automatic cataphoretic coating of heaters is designed to coat complex heaters with alundum by cataphoresis. This is a multi-position machine with periodic action. The cassette with heaters periodically moves between the positions of the machine, where operations are performed. The following operations are performed on this semi-automatic machine: cataphoretic coating of heaters; washing of heaters in acetone to remove drops of alundum paste and leaks formed in the heater loops; drying the coating in a jet of hot air; fixing the coating to increase its mechanical strength; final final drying. The calculation of the kinematic and pneumatic schemes of the machine was carried out, the calculation of the power of the carousel drive and the ma-chine, the Maltese mechanism of the carousel drive, belt and worm gears were calculated [1,2]. The graphic part of the project includes a kinematic diagram of the ma-chine, a general view of the machine with a drive, a drive mechanism, working drawings of two parts, specifications for the assembly drawing. In the economic part, the economy of the machine for manufacturing and oper-ation is determined, the feasibility of its development is determined. In the section "Occupational safety" measures are developed to improve the operation of the semi-automatic cataphoresis heater from the point of view of safety.
Development of a drive for a machine for cataphoresis of heaters
Keywords: 6.133.00.00; – катод; підігрівач; покриття; катафорез; привід; - cathode; heater; coating; cataphoresis; drive; calculation; eco-nomics; safety. List of used literature sources: 1. Kodra Yu.V.; Stotsko Z.A. Technological machines. Calculation and design: Textbook / Ed. Z.A. Stotsko. Second edition; supplemented. - Lviv: Publishing house "Beskyd Bit"; 2004. - 466 p. 2. Pavlishche V.T. Fundamentals of design and calculation of machine parts. – K.: Higher School; 1993. – 556 p. 3. Shvets E.D.; Yudachov A.V.; Truba M.M. Vacuum and plasma electronics. Part 1. Electronic devices. Textbook. Zaporizhzhia; ed. ZDIA; 2009; 258 p